2018
DOI: 10.12669/pjms.344.15411
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to the lack of interest in research activities among postgraduate medical students

Abstract: Objective:To determine the factors contributing to lack of interest in research activities among postgraduate residents in pediatric medicine.Methods:This cross-sectional survey was conducted at The Children’s Hospital Lahore, Pakistan in August 2017. The questionnaire was distributed to 105 postgraduate residents working in pediatric medicine department and 90 of them returned the completed proforma (response rate; 86%). Data was analyzed by SPSS version 22.Results:Out of 90 residents’ females were predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…We designed a 39-items questionnaire to explore the evaluation index of research capacity on the perspective of postgraduate students .The questionnaire consisted of items including demographics and other 34 items about index re ect one's scienti c research ability.The participants choose the number (1)(2)(3)(4)(5) according the importance of each items they think.1 means not important at all;2 means not important;3 means neutral;4 means important;5 means very important.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed a 39-items questionnaire to explore the evaluation index of research capacity on the perspective of postgraduate students .The questionnaire consisted of items including demographics and other 34 items about index re ect one's scienti c research ability.The participants choose the number (1)(2)(3)(4)(5) according the importance of each items they think.1 means not important at all;2 means not important;3 means neutral;4 means important;5 means very important.…”
Section: Methodsmentioning
confidence: 99%
“…In China, as in many other countries worldwide, postgraduate medical students' capability for scienti c research is an essential part of the educational system. Scienti c research can not only make students richer in their thought processes but also update students on the latest advances in medicine [5] and enhance their ability to solve problems, make decisions, and provide high-quality health care services. Therefore, developing the capability for scienti c research is a core feature of postgraduate education.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents of other research studies supported our observations where students reported lack of time as a major obstacle. 4,8,11,13 Medical students declare lengthy medical curriculum and intense terms of contact hours as a main reason behind not participating in scientific work. Similarly, it was the main issue of Amin research participants where time management was a major obstacle in their research work (62.4%).…”
Section: Bar Chart Presenting Barriers Towards Research Work Among Pgmentioning
confidence: 99%
“…[2][3][4][5] Globally, many developed and under developed countries have implemented compulsory courses that flourish and nurture positive attitude towards research. 6 Regardless of its importance, various researchers have pointed out barriers against scientific research so the number of researchers continues to dwindle worldwide, [7][8][9][10][11][12][13] Although investigators recognize barriers towards research work, however none of them has investigate the role of demographic view (age, gender, marital status and maternal education) on research work among PG trainees of medicine & dentistry. This study was therefore started to evaluate the effects of demographic views on research activities among postgraduate medical and dental students in 3 public center medical institutes.…”
Section: Introductionmentioning
confidence: 99%
“…Students do not spend ample time in reading research journals and articles leading to lack of knowledge and interest in research and research-based activities. (6,7,8,9) As a part of research, conducted at King Edward Medical University, it was found that most of the students showed lack of interest in Research .Factors contributing to lack of interest were ,most of students think research as useless activity, lack of internet facilities, time limitation, curriculum overload, lack of counselling, lack of knowledge and motivation, and uncooperative staff. (6) A recent study carried out at The Children's Hospital and The Institute of Child Health (ICH) Lahore, Pakistan showed lack of proper training for research and lack of previous exposure to research which shows that knowledge and understanding of research is necessary and essential otherwise it can be a barrier in future research activities.…”
Section: Trend Of Medical Research Journal and Article Reading Among mentioning
confidence: 99%